2016
DOI: 10.21776/ub.jpacr.2016.005.03.253
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Coordination Compounds of Silver(I) Nitrite with Ligands Ethylenethiourea and N,N'-diethylthiourea

Abstract: Coordination compound of silver (I) nitrate and ethylenethiourea (etu) in 1 : 4 stochiometry have been reported [1]. Coordination compound A and B being silver (I) nitrite with etu and silver(I) nitrite with N,N'-diethylthiourea (detu) respectively, have never been done. The purpose of this study is to synthesize and characterize coordination compounds A and B. Synthesis of coordination compounds A with 1 : 4 and B with 1 : 2 ratio stoichiometry respectively. Both of synthesis was conducted in acetonitrile dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…More study of the spectra confirmed the shape of crystalline compounds together with UV-Visible and infrared as well as magnetic susceptibility measurement. In other synthesis the X-ray spectra were used to calculate reactive tendency as well as shape of molecules [23][24][25] besides characterization. Another X-ray technique is the energy dispersive analysis by X-rays (EDX) which intensity is proportional to the amount of the elements.…”
Section: Methods For Chalcogen Materials Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…More study of the spectra confirmed the shape of crystalline compounds together with UV-Visible and infrared as well as magnetic susceptibility measurement. In other synthesis the X-ray spectra were used to calculate reactive tendency as well as shape of molecules [23][24][25] besides characterization. Another X-ray technique is the energy dispersive analysis by X-rays (EDX) which intensity is proportional to the amount of the elements.…”
Section: Methods For Chalcogen Materials Characterizationmentioning
confidence: 99%
“…Another X-ray technique is the energy dispersive analysis by X-rays (EDX) which intensity is proportional to the amount of the elements. The method is commonly combined with scanning electron microscopy (SEM) to get pre-experimental data, before the variables are given [22,24,26] or to characterize and give elemental confirmation [62].…”
Section: Methods For Chalcogen Materials Characterizationmentioning
confidence: 99%
See 3 more Smart Citations